FUNGAL INFECTION AND ALFLATOXIN CONTAMINATION IN STORED MEDICINAL PLANTS AT SOME HOSPITALS IN NGHE AN, AND INTERVENTION EFFECTIVENESS, 2019 (Vietnam Journal of Community Medicine, 2022)
Objectives: Fungal culture in Saboraud media was conducted to determine the prevalence of fungal infection in traditional medicinal plants. High performance liquid chromatography was applied to quantify alflatoxin. And the hospitals were invested equipment to change microclimate conditions so as to reduce the prevalence of fungal infection in traditional herbal remedies.Materials and methods: The study was designed using descriptive and laboratory methods. A total of 505 herbal medicine samples in the list of essential medicines regulated by the Circular 05/2015/TT-BYT were included for determination of fungal infection, and 262 positive specimens were tested for quantification of alflatoxin. Ten hospitals specializing in traditional medicines in Nghe An province were invested air conditioners, dehumidifiers, and ventilation systems.Results: The overall prevalence of fungal infection in medicinal plants was 51.8%; the overall prevalence of alflatoxin contamination was 4.75%; and the prevalence of alflatoxin in positive fungal cultures was 9.10%. The proportion of samples with alflatoxin exceeding the limit according to the Vietnam standard QCVN 8-1: 2011/BYT was 66.7% (16/24). 100% of the stores did not meet the microclimate conditions for preserving medicinal plants (average temperature > 30°C, average humidity > 70%, and average wind speed < 0.5m/s). 100% of the stores were not equipped with dehumidifiers and air conditioning systems.Conclusion: The prevalence of fungal infection in medicinal plants in the studied hospitals was as high as 51.8%. The equipment investment significantly reduced fungal infections from 51.8% to 18.99%.
Keywords: Fungi, herbal medicine, alflatoxin.